Vector Error Correction Modelling of the Composition of Government Spending and the Real Exchange Rate in Nigeria - Oriavwote, Victor E.; Omojimite, Ben U. (Richtmann Publishing, 2012)
The main objective of this study has been to empirically investigate the relationship between government expenditureand the Real Exchange Rate in Nigeria . Using data covering 1970 to 2010, the Vector Error Correction and Cointegration testsresults established a long run relationship among the components of government expenditure and the Real Exchange Rate. Theresult showed that government investment has delivered more productivity gains in the non-tradable sector than in the tradablesector, while an increase in government consumption increased the relative demand for non-tradable. The government shouldthus shift attention to the expansion of the tradable sector.